Peran Bidang Keilmuan Teknologi Pangan Dalam Upaya Bela Negara: The Role of the Scientific Field of Food Technology in Efforts to Defend the Country - Ifwarisan Defri; Yunita Satya Pratiwi; Pardi Tola (Abdi-mesin: Jurnal Pengabdian Masyarakat Teknik Mesin, 2022)
Defend the country in the food sector can be implemented in several ways, for example consuming national food or contributing in research, education and service related to the development of national food products. Any kinds of vocations or activities that have an impact on the advancement of the national food is defend the country attitude. In this counseling, an online survey was conducted using the google form, the survey involved 123 respondents. Respondents filled out a questionnaire by providing answers or opinions on a number of questions related to the implementation of defend the country in the field of food technology. The survey results show that 87% of respondents rate that implementation of defend the country in the field of food technology is very importance, and 13% of respondents consider is important. 84% of respondents believe that globalization does not really affect on the fondness of national food products, while 16% of respondents believe that globalization is the main factor of the fondness of national food products declining. 89% of respondents agree and 11% strongly agree that fondnessing national food products is an implementation of defend the country. Meanwhile, regarding the use of national food products, 67% of respondents think that they have not fully consumed national food products, while 33% of respondents think that they have fully consumed national food products. From the survey conducted, it can be concluded that the respondents have an understanding that defend the country can also be realized in the food sector by prefering and consuming national food products. In addition, respondents assessed that globalization has no significant effect on the national food products preference.